ELECTROPHYSICAL DIAGNOSIS OF THE LARGE SCALE INTEGRATION SUBMICRON STRUCTURES RELIABILITY BASED ON THE EFFECTS OF THE NONLINEARITY OF THEIR CHARACTERISTICS - Новосядлий, Степан Петрович; Фрик, Ольга Богданівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Nowadays the development of the world electronic industry is characterized by constant increase of the reliability requirements to the products of the solid-state electronics, microelectronics and optoelectronics. The search for the optimal ways of the fulfillment of these requirements showed the necessity of deep understanding of the physics of phenomena, which cause the breakdown of the LSI and increase of the importance of their reliability. The physical approach to the provision of the reliability of semi-conductors was formed in the 70-80-ies. Nowadays it should be also done for the submicron LSI structures. This is the problem we describe in our article.